Prediksi Erosi Berdasarkan Metode Universal Soil Loss Equation (Usle) Untuk Arahan Penggunaan Lahan Di Daerah Aliran Sungai Lawo - Nurul Apriani; Usman Arsyad; Baharuddin Mappangaja (Jurnal Hutan dan Masyarakat, 2021)
This study aims (1) to determine the ratio of the erosion value of the usle methods in the Lawo watershed (2) to plan soil and water conservation in the Lawo watershed. This research is based on mapping which is classified as non-experimental research using survey method. The erosion value was predicted using the Universal Soil Loss Equation (USLE) model. The results showed that land use in the Lawo watershed was secondary forest, plantation forest, dry land agriculture, dry land farming mixed with shrubs, shrubs, settlements and open land. The total erosion value for the USLE method is the average erosion that occurs. in the lawo river basin, namely 30948352.27 tonnes / year tonnes / year. Lawo watershed recovery plan in the form of land use patterns to reduce the rate of erosion, namely agroforestry dry land farming, while for settlements in the form of infiltration wells, enrichment of plants for plantation forest land use, refinement of bench terraces on paddy land use and terracing use accordingly the field, as well as reforestation and planting of land cover for the use of shrub land.